Cervical Intervertebral Disk to Vertebral Body Ratios of Different Dog Breeds Based on Sagittal Magnetic Resonance Imaging - Düver, Pia; Precht, Christina; Fosgate, Geoffrey; Forterre, Franck; Hettlich, Bianca (Frontiers in Veterinary Science, 2018)
Objective: To establish sagittal area and length reference values and ratios between apparently normal canine cervical vertebrae and intervertebral disks using magnetic resonance imaging. Sample: Retrospective evaluation of cervical vertebral column magnetic resonance imaging studies of 44 dogs representing 5 different breeds (Labrador Retriever, n=10; French Bulldog, n=10; Great Dane, n=9; Chihuahua, n=10; Dachshund, n=5). Procedures: Mid-sagittal measurements of vertebral body and disk areas were obtained from C3 through C7 vertebrae and C2/C3 through C6/C7 intervertebral disks. Disk to vertebra area ratios were calculated and compared among dog breeds. Additionally, sagittal vertebral body and disk length measurements were obtained and disk to vertebra length ratios calculated. Inter and intra observer variability was assessed. Results: There were significant differences for disk to vertebral body area and length ratios between evaluated dog breeds and cervical vertebral locations (p < 0.001). Mean area ratio of Chihuahuas was significantly larger than all other breeds, while results from Dachshunds were only significantly different than Chihuahuas and Labrador Retrievers. Mean area ratios were statistically different between the cranial and caudal cervical vertebral locations. Regarding length ratios, results from Chihuahuas were significantly different than all breeds except Dachshunds. Mean length ratios were statistically different between all cervical locations, except C2/C3 compared to C3/C4. Intra- and interobserver variability was very good to excellent. Conclusion and Clinical Relevance: There are significant differences in area and length ratios between dog breeds. Differences also exist in area and length ratios between the cranial and caudal cervical vertebral column. These differences may play a role in the development of vertebral column diseases including intervertebral disk disease.